Development of an Arduino-Based Water Level Indicator with Audio-Visual Alert Mechanisms - Hidayatullah, Achmad Syauqii; Normalisa (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
Monitoring water levels in tanks and reservoirs is essential to prevent overflow, dry running of pumps, and inefficient water usage. This study presents the design and implementation of a low-cost water level indicator and alert system based on Arduino, integrating a water level sensor, RGB LED indicators, and an audible buzzer. The proposed system detects discrete water levels using conductive probes or a resistive water level sensor placed at different heights inside a container. The Arduino microcontroller processes the sensor signals and provides real-time visual feedback through an RGB LED, where different colors represent low, medium, and high water levels. In addition, a buzzer is activated when the water reaches a critical threshold, serving as an audible warning to prevent overflow or system damage. The system architecture is simple, modular, and easy to implement, making it suitable for domestic water tanks, laboratories, and small-scale industrial applications. Experimental testing demonstrates that the system responds reliably to changes in water level, with minimal latency and stable operation under repeated trials. Compared to conventional mechanical float-based indicators, the proposed design offers improved flexibility, ease of maintenance, and expandability, such as integration with wireless modules or IoT platforms. The results show that combining visual (RGB LED) and audio (buzzer) indicators enhances user awareness and system usability. Overall, this Arduino-based water level indicator provides an effective, economical, and scalable solution for real-time water level monitoring and alerting, supporting efficient water management and resource conservation.